Religious Populism and Public Sphere in Indonesia - Robertus Wijanarko (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
Religious populism has strong and profound influence in Indonesia. Itchallenges the rational foundation of the democratic structure of theIndonesian Politics. This populist political movement utilizes religiouslanguage and symbols as their language of political articulation, negotiation,and contestation, which then occupies the real and virtual public sphere ofthe politics of Indonesia. Therefore, this use of religious language andsymbols has placed democratic system in a serious risk. This critical study isintended to investigate the disadvantages of the use of religious language andsymbols in the political arena in Indonesia. I will employ Paul Ricour’sthoughts in his writing, The Fragility of Political Language, as a lens ofanalysis for that phenomenon. Through that analysis I argue that the use ofreligious language and symbols in political discourse contradicts theprovisional character of political language in democratic political settings. Isuggest, therefore, the reenactment of the constitutional and rationalfoundation of democratic structure of Politics in Indonesia is seriouslyrequired.